2018
DOI: 10.1155/2018/5961913
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Ciliated Cyst in an Unusual Location: Between Two Scapulas

Abstract: Cutaneous ciliated cyst is defined as a rare, painless lesion frequently encountered on the lower extremities of young girls after puberty. The cyst is surrounded by the columnar ciliary epithelium. Apart from the lower extremities of girls, they may be localized on the scalp, scapula, thumb, abdomen, umbilicus, thigh, heel, knee, and gluteal region. There are two theories to explain this localization. The first is that they are mullerian heterotrophy, while the other is that they are ciliated metaplasia of ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Consequently, during menarche hormonal stimulation plays a role in the growth of those cystic formations (2)(3)(4)(5). A second theory, concerning the etiological background of this entity, supports the cilia metaplasia of the eccrine glands.…”
Section: Discussionmentioning
confidence: 95%
“…Consequently, during menarche hormonal stimulation plays a role in the growth of those cystic formations (2)(3)(4)(5). A second theory, concerning the etiological background of this entity, supports the cilia metaplasia of the eccrine glands.…”
Section: Discussionmentioning
confidence: 95%
“…In our case, the cyst was overlying the gluteal area, it measured 4 cm in the greatest dimension and was non tender, these findings were in concordance with the findings in literature. 6 The lesions typically measured several centimeters in diameter and presented as unilocular or multilocular cysts. A study describing the cysts histologically, reported that the cysts are typically lined by ciliated cuboidal to columnar epithelium with pseudostratified areas and that focal squamous metaplasia is occasionally present.…”
Section: Discussionmentioning
confidence: 99%
“…3 Previous reports indicated the cysts as varying from 1 to 4 cm in size, and the cysts are generally soft in texture and non tender masses. 6 The etiology is yet to be completely understood, however so far there are few theories that are still being studied. The first is that they are an ectopic mullerian residue as they resemble the fallopian tube epithelial lining.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations